Language dynamics in the agricultural sector: Determining language use and choices in a Malaysian organization - Sareen Kaur Bhar, A/P Lakhbir Singh; Zuraina, Ali; Norshima, Zainal Shah (Transnational Press London Ltd, 2024)
In light of globalization and international trade, English plays a predominant role in the agricultural sector. Effective communication in English is essential for agricultural professionals, especially those involved in international markets. However, limited research has been conducted on the linguistic needs of these professionals. This study investigates the extent of English and other language usage across various communication channels within an agricultural organization. Using a mixed-method approach, data were collected through questionnaires and interviews from employees of a multinational agricultural company. The results indicate a flexible language policy where both Bahasa Melayu and English are used contextually, depending on the situation and organizational interests. The study reveals that while English is crucial for formal communication and professional advancement, adaptability to the multilingual context is vital for maintaining operational efficiency and fostering inclusive workplace communication. These findings provide insights into language use in agricultural companies in multilingual countries like Malaysia, emphasizing the need for continuous language training to bridge proficiency gaps.